EVA foam recycled material-alpha-methyl acrylic acid copolymer, and preparation method and application thereof

CN119859221BActive Publication Date: 2026-11-03HUAQIAO UNIVERSITY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510120104.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2026-11-03
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

Existing technologies for the reuse of recycled EVA foam materials have shortcomings such as high energy consumption and unstable results. The poor compatibility between recycled EVA foam materials and the matrix leads to a decline in the performance of composite materials.

Method used

An aqueous grafting method using methacrylic acid was employed to initiate the reaction between recycled EVA foam and methacrylic acid monomers via an initiator, thereby preparing an EVA foam-α-methacrylic acid copolymer and improving its compatibility with other components.

Benefits of technology

It improves the compatibility and overall performance of recycled EVA foam, reduces production costs and environmental pollution risks, broadens its application range, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859221B_ABST
    Figure CN119859221B_ABST
Patent Text Reader

Abstract

The application discloses an EVA foam recycled material-alpha-methacrylic acid copolymer and a preparation method and application thereof, the grafting degree of the EVA foam recycled material-alpha-methacrylic acid copolymer is 0.6-7.3%, and the EVA foam recycled material-alpha-methacrylic acid copolymer is prepared by mixing and drying raw material components including the following components in parts by weight: 2 parts by weight of powdery EVA foam recycled material, 0.03-0.1 parts by weight of an initiator, 0.8-1.6 parts by weight of a methacrylic acid monomer and 20 parts by weight of deionized water. The EVA foam recycled material is grafted with alpha-methacrylic acid on the surface, and the chemical structure endows the material with extremely high activity and polarity; due to the introduction of alpha-methacrylic acid, the EVA foam recycled material can form stronger interaction with other components, thereby significantly improving the compatibility and functionality of the EVA foam recycled material in a composite material. In addition, the grafting method is simple and green, and has extremely important application significance for the reuse of the EVA foam recycled material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of modified EVA technology, specifically relating to an EVA foam recycled material-α-methacrylic acid copolymer, its preparation method, and its application. Background Technology

[0002] With the rapid development of industry and the social economy, EVA (ethylene-vinyl acetate copolymer), as a high-molecular polymer material, is widely used due to its good plasticity, elasticity, and processability. Especially after foaming, EVA materials have advantages such as low density, excellent mechanical properties, and easy coloring, and are therefore often used to manufacture various foamed shoe sole materials. However, in the production process of EVA foam materials and their products, due to size and shape requirements, a large amount of scrap and defective products are inevitably generated. These waste materials already contain fillers, colorants, rubber and plastic additives, and other auxiliary materials. Because of the complex composition of EVA foam materials, efficient recycling and reuse are difficult to achieve. Therefore, developing efficient EVA foam recycling and reuse technologies is of significant practical importance.

[0003] During the foaming process, the molecular chains of EVA foam form a highly cross-linked three-dimensional network structure. This structure endows the foam with heat resistance, corrosion resistance, and infusibility, but it also presents significant challenges to the recycling and reuse of EVA foam. In typical recycling technologies, recycled EVA foam is usually combined with new polymers to form composite materials. In this technology, the strength of the interaction between the recycled EVA and the matrix directly determines the performance of the composite material. Ideally, the recycled EVA should form a strong interaction with the matrix. However, recycled EVA foam is usually already cross-linked, structurally stable, and inert, resulting in poor compatibility with the matrix. Increasing the amount of recycled EVA often reduces the mechanical properties of the composite material.

[0004] To address this issue, some researchers have attempted to process recycled EVA foam using high-temperature shearing or melt extrusion methods. For example, CN118085437A discloses a recycling method based on the decrosslinking of recycled EVA foam and its application. This method expands the three-dimensional crosslinked network of the recycled EVA foam using a solvent expansion method, and then uses 2,2'-dithiodibenzoic acid as a decrosslinking agent to uniformly penetrate the crosslinked network in a solvent. Through the high-temperature shearing action of equipment such as a twin-screw extruder, the sulfur free radicals generated by the decrosslinking agent combine with the active free radicals generated when the crosslinked network is destroyed, thereby obtaining decrosslinked recycled EVA foam. This process can improve the compatibility of recycled EVA with the new polymer matrix to a certain extent, achieving a better recycling and reuse effect, but its energy consumption is high.

[0005] Furthermore, CN114835973A proposes an EVA composite foam material prepared from recycled EVA foam and its preparation process. This method modifies the recycled EVA foam material by grafting thermoplastic starch and maleic anhydride onto high-density polyethylene (HDPE), and then uses extrusion granulation technology to blend and melt EVA resin, styrene-ethylene-butene-styrene block copolymer (SEBS), and the modified recycled EVA foam material to obtain the final EVA composite foam material. The essence of this method is to improve the compatibility of recycled EVA with other polymer components through maleic anhydride grafting modification. However, this process is also relatively energy-intensive, and the improvement effect is not stable enough.

[0006] In summary, although various methods have been attempted to solve the problem of reusing recycled EVA foam, existing technologies still have shortcomings such as high energy consumption and unstable results. Summary of the Invention

[0007] The purpose of this invention is to overcome the defects of the prior art and provide an EVA foam recycled material-α-methacrylic acid copolymer.

[0008] Another object of the present invention is to provide a method for preparing the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer.

[0009] Another object of the present invention is to provide the application of the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer.

[0010] The technical solution of the present invention is as follows:

[0011] An EVA foam recycled material-α-methacrylic acid copolymer with a grafting degree of 0.6-7.3% is prepared by mixing and drying raw material components comprising the following parts by weight:

[0012] 2 parts by weight of powdered recycled EVA foam

[0013] Initiator 0.03-0.1 parts by weight

[0014] 0.8-1.6 parts by weight of methacrylic acid monomer

[0015] 20 parts by weight of deionized water.

[0016] In a preferred embodiment of the present invention, the initiator is selected from benzoyl peroxide (BPO), dicumyl peroxide (DCP), and tert-butyl peroxide-2-ethylhexyl carbonate.

[0017] More preferably, the initiator is benzoyl peroxide.

[0018] The preparation method of the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer includes the following steps:

[0019] (1) A pre-reaction mixed solution was prepared by mixing powdered EVA foam recycled material, deionized water, initiator and methacrylic acid monomer;

[0020] (2) The pre-reaction mixture obtained in step (1) is placed under nitrogen protection and heated to carry out the reaction;

[0021] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried to obtain the EVA foam recycled material-α-methacrylic acid copolymer.

[0022] In a preferred embodiment of the present invention, in step (2), the temperature is raised to 70-95°C and the reaction is carried out for 1-6 hours.

[0023] More preferably, in step (2), the temperature is raised to 75-95°C and the reaction is carried out for 1-2 hours.

[0024] The above-mentioned EVA foam recycled material-α-methacrylic acid copolymer is used as a shoe material.

[0025] In a preferred embodiment of the present invention, the shoe material includes a shoe sole and a shoe upper.

[0026] A shoe having the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer.

[0027] The beneficial effects of this invention are:

[0028] 1. The EVA foam recycled material of the present invention is grafted with α-methacrylic acid on its surface. This chemical structure endows the material with extremely high activity and polarity. Due to the introduction of α-methacrylic acid, the EVA foam recycled material can form stronger interactions with other components, thereby significantly improving its compatibility and functionality in composite materials. In addition, the grafting method is simple and environmentally friendly, which has extremely important application significance for the reuse of EVA foam recycled materials.

[0029] 2. This invention uses water as the reaction medium, completely eliminating the large amounts of organic solvents used in traditional processes. This improvement not only reduces environmental pollution from organic solvent volatilization but also lowers safety risks during production.

[0030] 3. Through grafting, this invention can effectively improve the mechanical properties, thermal stability, and weather resistance of recycled EVA foam. The grafted recycled EVA foam exhibits superior overall performance in subsequent applications, meeting higher industrial standards and thus broadening its application range.

[0031] 4. The grafting reaction of this invention is carried out under aqueous phase conditions, which are mild and do not require high temperature, high pressure, or complex equipment. This reaction method can easily graft methacrylic acid onto recycled EVA foam. The reaction process is simple, feasible, easy to operate and control, energy-saving, environmentally friendly, and low-cost, making it suitable for large-scale industrial production.

[0032] 5. During the grafting process, this invention generates relatively few byproducts. This feature not only simplifies the complexity of waste treatment but also reduces waste generation, further lowering production costs and environmental burden. Attached Figure Description

[0033] Figure 1 This is a flowchart of the preparation process according to an embodiment of the present invention.

[0034] Figure 2 The images show the infrared test results of the methacrylic acid modified EVA foam recycled material prepared in Example 1 of the present invention, the unmodified methacrylic acid EVA foam recycled material in Comparative Example 1, and polymethacrylic acid.

[0035] Figure 3 The thermogravimetric analysis (TGA) results are shown for the methacrylic acid-modified EVA foam recycled materials prepared in Examples 1 and 6 of this invention, the unmodified EVA foam recycled materials in Comparative Example 1, and polymethacrylic acid.

[0036] Figure 4 The figures show the water contact angle test results of the methacrylic acid-modified EVA foam recycled material prepared in Example 1 and the unmodified EVA foam recycled material in Comparative Example 1. The left figure represents Comparative Example 1, and the right figure represents Example 1. Detailed Implementation

[0037] The technical solution of the present invention will be further explained and described below with reference to specific embodiments and accompanying drawings.

[0038] The preparation process flow of the following embodiments is as follows: Figure 1 As shown, the grafting degree is calculated as (weight gain of recycled EVA foam / original weight of recycled EVA foam) × 100%.

[0039] Example 1

[0040] (1) Weigh 2g of powdered EVA foam recycled material (300 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.1g of benzoyl peroxide and 1.6g of methacrylic acid monomer;

[0041] (2) The pre-reaction mixed solution obtained in step (1) was placed under nitrogen protection and heated to 75°C for 1.5 h.

[0042] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0043] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 4.85%.

[0044] Example 2

[0045] (1) Weigh 2g of powdered EVA foam recycled material (200 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.1g of benzoyl peroxide and 1.6g of methacrylic acid monomer;

[0046] (2) The pre-reaction mixed solution obtained in step (1) was placed under nitrogen protection and heated to 85°C for 1.5 h.

[0047] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0048] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 6.35%.

[0049] Example 3

[0050] (1) Weigh 2g of powdered EVA foam recycled material (400 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.1g of benzoyl peroxide and 1.6g of methacrylic acid monomer;

[0051] (2) The pre-reaction mixture obtained in step (1) was placed under nitrogen protection and heated to 95°C for 1.5 h.

[0052] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0053] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 7.25%.

[0054] get

[0055] Example 4

[0056] (1) Weigh 2g of powdered EVA foam recycled material (20 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.1g of benzoyl peroxide and 1g of methacrylic acid monomer;

[0057] (2) The pre-reaction mixed solution obtained in step (1) was placed under nitrogen protection and heated to 75°C for 1.5 h.

[0058] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0059] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 3.76%.

[0060] Example 5

[0061] (1) Weigh 2g of powdered EVA foam recycled material (100 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.1g of benzoyl peroxide and 0.8g of methacrylic acid monomer;

[0062] (2) The pre-reaction mixed solution obtained in step (1) was placed under nitrogen protection and heated to 75°C for 1.5 h.

[0063] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0064] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 3.1%.

[0065] get

[0066] Example 6

[0067] (1) Weigh 2g of powdered EVA foam recycled material (400 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.06g of benzoyl peroxide and 1.6g of methacrylic acid monomer;

[0068] (2) The pre-reaction mixed solution obtained in step (1) was placed under nitrogen protection and heated to 75°C for 1.5 h.

[0069] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0070] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 2.37%.

[0071] Example 7

[0072] (1) Weigh 2g of powdered EVA foam recycled material (250 mesh), and prepare a pre-reaction mixed solution with 20g of deionized water, 0.03g of benzoyl peroxide and 1.6g of methacrylic acid monomer;

[0073] (2) The pre-reaction mixed solution obtained in step (1) was placed under nitrogen protection and heated to 75°C for 1.5 h.

[0074] (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.

[0075] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this embodiment was measured by the weight gain method, and the grafting degree was found to be 0.6%.

[0076] Comparative Example 1

[0077] Unmodified EVA foam recycled material

[0078] A. Infrared spectroscopy was performed on the methacrylic acid-modified EVA foam recycled material prepared in Example 1, and on the unmodified EVA foam recycled material and polymethacrylic acid in the comparative example. The results are as follows: Figure 2 As shown, the main absorption bands of the recycled EVA material can be observed, namely those associated with acetate and vinyl groups. Figure 2 In the absorption band of PMAA, an absorption band at 1695 cm⁻¹ can be observed. -1 There is an absorption peak at 966 cm⁻¹, which represents the characteristic absorption band of the carbonyl (C=O) double bond in methacrylic acid. After the grafting reaction, compared with the original EVA recycled material, a significant difference can be observed in the grafted sample at 966 cm⁻¹. -1 A new peak appeared at 1695 cm⁻¹, which is the characteristic absorption peak of -OH on methacrylic acid; and at 1695 cm⁻¹... -1 A new peak appeared on the left and right EVA recycled materials, which is also the characteristic absorption peak of C=O on methacrylic acid, indicating that methacrylic acid was successfully attached to the EVA recycled materials.

[0079] B. Thermogravimetric analysis (TGA) was performed on the methacrylic acid-modified EVA foam recycled materials prepared in Examples 1 and 6, the unmodified EVA foam recycled material in Comparative Example 1, and polymethacrylic acid. The results are as follows: Figure 3As shown, the first weight loss of the EVA recycled material between 300 and 360°C is related to the decomposition of vinyl acetate. A second weight loss occurred at temperatures above 420°C, which is related to the decomposition of the ethylene moiety in the EVA copolymer. PMAA experienced a 20% weight loss at 200-250°C, indicating carboxyl group degradation, while the remaining weight loss at 400°C is related to the pyrolysis of the PMAA backbone. The MAA-grafted EVA recycled material sample began to show weight loss at 200°C, and a second weight loss occurred at 400°C, exhibiting the same plateau in weight loss, indicating successful MAA grafting onto the EVA foam. Furthermore, the thermal stability of the EVA recycled material decreased with increasing grafting amount.

[0080] C. Water contact angle tests were performed on the methacrylic acid-modified EVA foam recycled material prepared in Example 1 and the unmodified EVA foam recycled material in the comparative example. The results are as follows: Figure 4 As shown, by testing the water contact angle of recycled EVA and grafted recycled EVA, it can be found that the water contact angle of the EVA recycled material grafted with methacrylic acid is reduced. This is because the surface of the added methacrylic acid contains oxygen-containing functional groups such as hydroxyl and carboxyl groups. The presence of these hydrophilic groups increases the hydrophilicity of the recycled EVA itself.

[0081] The above description is merely a preferred embodiment of the present invention, and therefore should not be construed as limiting the scope of the present invention. All equivalent changes and modifications made in accordance with the scope of the patent and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing an EVA foam recycled material-α-methacrylic acid copolymer, characterized in that: Prepared and dried from a mixture of raw material components comprising the following parts by weight: 2 parts by weight of powdered recycled EVA foam Initiator 0.03-0.1 parts by weight 0.8-1.6 parts by weight of methacrylic acid monomer 20 parts by weight of deionized water; The preparation method includes the following steps: (1) A pre-reaction mixed solution was prepared by mixing powdered EVA foam recycled material, deionized water, initiator and methacrylic acid monomer; The water contact angle of the powdered EVA foam recycled material is 132.94°; The initiator is selected from benzoyl peroxide; (2) The pre-reaction mixture obtained in step (1) is placed under nitrogen protection and heated to carry out the reaction; (3) The reaction product obtained in step (2) is washed and filtered multiple times, and then dried to obtain the EVA foam recycled material-α-methacrylic acid copolymer; The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer is 4.85-7.3%.

2. The method for preparing an EVA foam recycled material-α-methacrylic acid copolymer as described in claim 1, characterized in that: In step (2), the temperature is raised to 75-95°C and the reaction is carried out for 1-6 hours.

3. The method for preparing an EVA foam recycled material-α-methacrylic acid copolymer as described in claim 1, characterized in that: In step (2), the temperature is raised to 75-95°C and the reaction is carried out for 1-2 hours.

4. The EVA foam recycled material-α-methacrylic acid copolymer prepared by the method of any one of claims 1 to 3 is used as a shoe material.

5. The application as described in claim 4, characterized in that: The shoe materials include shoe sole materials and shoe upper materials.

6. A shoe, characterized in that: The EVA foam recycled material-α-methacrylic acid copolymer prepared by the method of any one of claims 1 to 3.

Citation Information

Patent Citations

  • Decrosslinking modified elastomer regenerated material as well as regeneration method and application thereof

    CN118420837A